2016
DOI: 10.9738/intsurg-d-16-00192.1
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-Term Outcomes of Pancreatic Resection for Pancreatic Adenocarcinoma in Patients Older Than 75 Years

Abstract: The short-and long-term outcomes of pancreatic resection for pancreatic adenocarcinoma have not been fully evaluated in elderly patients. This retrospective study selected patients who underwent curative surgery for pancreatic cancer at our institution. Patients were categorized into 2 groups: nonelderly patients (age , 75 years; group A) and elderly patients (age 75 years; group B). The surgical morbidity, surgical mortality, overall survival (OS), and recurrence-free survival (RFS) rates in the 2 groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In 2012, a meta-analysis reported that elderly patients experience higher rates of postoperative complications and mortality [6]. Other manuscripts, afterward, found that pancreatic surgery has similar safety and efficacy profiles in elderly versus non-elderly [7][8][9][10]. Regarding minimally invasive pancreaticoduodenectomy, data analysis on 1768 elderly patients submitted to laparoscopic versus open pancreaticoduodenectomy from the United States National Cancer Dabatase showed that minimally invasive cases experience lower mortality rates [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, a meta-analysis reported that elderly patients experience higher rates of postoperative complications and mortality [6]. Other manuscripts, afterward, found that pancreatic surgery has similar safety and efficacy profiles in elderly versus non-elderly [7][8][9][10]. Regarding minimally invasive pancreaticoduodenectomy, data analysis on 1768 elderly patients submitted to laparoscopic versus open pancreaticoduodenectomy from the United States National Cancer Dabatase showed that minimally invasive cases experience lower mortality rates [11].…”
Section: Introductionmentioning
confidence: 99%